2002
DOI: 10.1046/j.1365-2885.2002.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of orally administered trimethoprim and sulfadiazine into noninfected subcutaneous tissue chambers in adult ponies

Abstract: The distribution of trimethoprim (TMP) and sulfadiazine (SDZ) into subcutaneously implanted noninfected tissue chambers was studied in healthy adult ponies. Six ponies were given an oral TMP/SDZ paste formulation at a dose of 5 mg/kg TMP and 25 mg/kg SDZ at 12 h intervals for 2 days in order to reach steady-state concentrations. Plasma concentrations and tissue chamber fluid (TCF) concentrations of both drugs were measured at regular intervals during a period commencing 24 h after the last oral administration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 13 publications
(24 reference statements)
1
24
0
Order By: Relevance
“…In the present study, we observed a slow rise and a slow decline in ampicillin concentrations in TCF, similar to the findings of Ensink et al. (1996a) and a feature that is considered characteristic for TCF (Bengtsson & Greko, 2002; Van Duikeren et al. , 2002).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we observed a slow rise and a slow decline in ampicillin concentrations in TCF, similar to the findings of Ensink et al. (1996a) and a feature that is considered characteristic for TCF (Bengtsson & Greko, 2002; Van Duikeren et al. , 2002).…”
Section: Discussionsupporting
confidence: 90%
“…In an earlier pharmacokinetic study with uninfected tissue chambers, drug concentrations were approximately 1 μ g/mL TMP and 20 μ g/mL SDZ throughout the dosing interval of 12 h (van Duijkeren et al. , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…On D1 and D3 the concentrations in these two ponies had also reached the levels of 1 μ g/mL TMP and 20 μ g/mL SDZ. On the basis of these concentrations it would be expected that this dosage regimen would be effective against all susceptible bacteria, with MIC s of ≤0.5/9.5 μ g/mL of TMP/SDZ (van Duijkeren et al. , 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The combination of a sulfonamide with trimethoprim results in bactericidal activity with lower MICs for each drug. 4 A study 5 evaluating trimethoprim-sulfadiazine paste administered orally to healthy adult ponies indicated that a dosage of 30 mg/ kg administered twice daily results in continuous therapeutic concentrations in subcutaneous tissue chambers for 12 hours. 3 When administered at a dosage of 30 mg/kg (13.6 mg/lb) orally twice daily, therapeutic plasma concentrations are maintained.…”
mentioning
confidence: 99%